Narirutin treatment accelerates the process of diabetic wound repair by regulating phenotype switching of macrophages through affecting metabolic reprogramming - Liu, Liang; Wang, Han; Zhou, Juan; Lu, Jing; Zhang, Yan; Liu, Haiyan; Lu, Li (Frontiers in Pharmacology, 2025)
IntroductionDiabetic foot ulcer (DFU) is one of the most common complications of diabetes, with substantial morbidity and mortality. Narirutin (Nar), a bioactive phytochemical derived from citrus peel, has been suggested to possess anti-inflammatory abilities. However, the involvement of Nar in DFU development remains poorly understood.MethodsThe polarization traits of bone marrow derived macrophages (BMDMs) with indicated treatments were determined by flow cytometry, immunofluorescence staining, western blot and qRT-PCR. Levels of lactate and α-ketoglutarate were measured for investigating the metabolic profiles. The cutaneous wounds of diabetic mice were established for evaluating the promotive roles of Nar in wound healing in vivo.ResultsWe found that high glucose treatment significant elevated the contents of TNF-α and IL-1β and lactate and reduced the levels of TGF-β1 and IL-4 and α-ketoglutarate in BMDMs. Then, Nar intervention effectively induced BMDMs repolarization from M1 to M2 state and the molecular mechanism was ascribed to drug-elicited activation of AMPK, which in turn increased the expression of downstream Mfn2, thereby enhancing the activity of oxidative phosphorylation and GATA3 cascade activation and disrupting the progress of glycolysis and NF-κB axis activation. Subsequently, we discovered that Nar injection effectively enhanced the healing rate of skin wounds in diabetic mice. Histological analysis showed that Nar dose-dependently induced dermis growth and collagen deposition in the wound area. Via activating AMPK/Mfn2 axis, Nar inhibited the activity of glycolysis and enhanced the extent of oxidative phosphorylation, accompanied by inflammation repression and angiogenesis promotion in the damaged tissueDiscussionOur study discovered that macrophages repolarization to M2 phenotype was required for Nar-induced promotive effects on diabetic wound repair by regulating reprogramming of glucose metabolism via mediating AMPK/Mfn2 pathway, providing a promising strategy for DFU management.